Application of Geographic Information Systems - Monwar Alam, Bhuiyan (IntechOpen, 2012)
The importance of Geographic Information Systems (GIS) can hardly be overemphasized in today's academic and professional arena. More professionals and academics have been using GIS than ever - urban & regional planners, civil engineers, geographers, spatial economists, sociologists, environmental scientists, criminal justice professionals, political scientists, and alike. As such, it is extremely important to understand the theories and applications of GIS in our teaching, professional work, and research. "The Application of Geographic Information Systems" presents research findings that explain GIS's applications in different subfields of social sciences. With several case studies conducted in different parts of the world, the book blends together the theories of GIS and their practical implementations in different conditions. It deals with GIS's application in the broad spectrum of geospatial analysis and modeling, water resources analysis, land use analysis, infrastructure network analysis like transportation and water distribution network, and such. The book is expected to be a useful source of knowledge to the users of GIS who envision its applications in their teaching and research. This easy-to-understand book is surely not the end in itself but a little contribution to toward our understanding of the rich and wonderful subject of GIS.